Reorientation of Teachers Teaching in Rural Areas - Kabra, Roop N. (JOURNAL OF INDIAN EDUCATION, 2010)
There is need of the teachers for providing proper school education in rural areas. Many field experience reveal that teachers often focus on the urban and feel comfortable in urban areas. It is necessary for the teachers to play a vital role in bringing awareness to the rural areas. As a democratic society we need interdependency among the people in sharing the ideals, institutions and experiences. Developing countries like India needs to develop proper linkages between rural-urban educational settings so that it will bring equity in the society.